Sistem Penghantaran Mel Negeri Selangor (Di Bawah Kendalian Pusat Mel Bukit Raja) - Nor Hisham, Haron (2002)

(untitled)
Postal service is one of the most popular mailing services in Malaysia. Majority of Malaysians used this service to send or delivers their letters, products, telegrams and the like. Therefore a research on mailing services was conducted in Bukit Raja Mailing Center to determine the efficiency of the service and to analyse on the delivery system in each of the depot involve in the state of Selangor. Analysis was carried out on the data concerning the process time and travelling time from depot to depot. There were eight routes all together in which each route is divided into two periods namely the morning period and evening period. The result of the analysis is recommended an alternative route that will increase efficiency. Two models were used in this research. There are the Networking and Computer Simulation model. Comparison was made between the model suggested and the existing one in order to evaluate the result. This research shows that the suggested alternative route is capable in reducing the time and distance of the service in each route.